Determination of fenazaquin in water and tomato matrices by GC-MS after a combined QuEChERS and switchable solvent liquid phase microextraction - Turan, Nouha Bakaraki; Maltepe, Esra; Chormey, Dotse Selali; Bakirdere, Sezgin (SPRINGER, 2020)
This study presents the use of Quick Easy Cheap Efficient Rugged and Safe (QuEChERS) as an effective sample cleaning procedure and switchable solvent liquid phase microextraction (SS-LPME) as a preconcentration tool for the determination of fenazaquin by gas chromatography mass spectrometry (GC-MS) at ultratrace levels. After a thorough optimization process, 0.50 mL of switchable solvent, 1.5 mL of 1.0 M sodium hydroxide, and 15 s of vortexing were determined as optimum conditions of the SS-LPME method. The limit of detection (LOD) and limit of quantitation (LOQ) determined using the optimum method (SS-LPME/GC-MS) were 0.05 and 0.18 ng/mL, respectively. Compared with direct GC-MS determination of fenazaquin, the optimum method yielded about 800-fold enhancement in detection power of GC-MS. The method was applied to lake, irrigation canal, well, and wastewater samples. In order to test the method's applicability on fresh tomato samples, a QuEChERS method was used before applying the SS-LPME method. Matrix-matched calibration standards were used to enhance the accuracy of fenazaquin quantification in spiked tomato samples to obtain recovery results close to 100%.
Keywords: Fenazaquin; GC-MS; Switchable solvent extraction; QuEChERS; Water; GAS-CHROMATOGRAPHY; PESTICIDE-RESIDUES; HUMAN HEALTH; EXTRACTION; SAMPLES; OPTIMIZATION; DESIGN; JUICE; TEA; Environmental Sciences & Ecology